Implementasi Perilaku Kewarganegaraan Sebagai Mediasi Pengaruh Keterikatan Pegawai, Efikasi Diri Terhadap Kinerja Karyawan Pada PT Application Solutions - Laura, Netty (Universitas Bunda Mulia, 2024)
Human resources are an important asset in a company, because human resources determine the success of a company. Human resource management and improving human resource performance have become the main focus of every company to encourage competitiveness in the future. A high-performing employee can make a significant contribution to achieving organizational goals. Currently, many companies have paid attention to factors to improve employee performance, including employee engagement and employee self-efficacy. This research aims to analyze the influence of employee engagement (X1) and self-efficacy (X2) through organizational citizenship behavior (OCB) (Z) as a mediating variable on the performance (Y) of PT Application Solutions employees. The research population included 115 employees, and the sampling technique used was a saturated sample, involving the entire population of PT Application Solutions. Data analysis in this research was carried out using the Partial Least Square (PLS) method with the support of SmartPLS 4 software. The findings indicate that, although the employee engagement variable has a positive influence, it does not reach a level of significance on employee performance. Additionally, employee engagement has a positive and significant influence on Organizational Citizenship Behavior (OCB). Furthermore, the self-efficacy variable has a positive and significant influence on employee performance and OCB. There is a positive and significant influence of the OCB variable on employee performance. Moreover, the OCB variable succeeded in being an effective mediator, connecting employee engagement and self-efficacy to employee performance, providing a positive and significant impact.